Addie-based development of islamic religious education learning videos for students at madrasah aliyah daarul khair, north lampung - Imam Aris Faisal; Romi Ma’ali; Pepen Supendi; M. Nasir; Yuyun Yuningsih (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to develop video-based learning media for the Islamic Religious Education (Pendidikan Agama Islam/PAI) subject to improve students’ understanding at Madrasah Aliyah Daarul Khair, North Lampung. The research was motivated by students’ low learning interest in PAI, which is often perceived as monotonous and less engaging. This study employed a Research and Development (R&D) approach using the ADDIE development model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The development process involved validation by subject matter experts and media experts using structured validation instruments. The validation results showed an average score of 4.5 out of 5 from subject matter experts and 4.6 out of 5 from media experts, indicating that the learning video is highly valid and feasible for instructional use. The implementation stage involved X and XI students of Madrasah Aliyah Daarul Khair, and the results demonstrated a significant increase in students’ learning interest and understanding after using the video-based media. Therefore, the developed learning video can be considered an effective alternative learning medium for enhancing the quality of Islamic Religious Education at the Madrasah Aliyah level.